Causal Euphoria Ritual Yajña (CERiYa) Di Kalangan Generasi Muda Hindu Di Bali - Oka Widana, Anak Agung Gde (Jurnal Penelitian Agama Hindu, 2025)
Causal Euphoria of Yajña Ritual is a term coined by the researcher himself that refers to the accumulation of various phenomena in the implementation of yajña by Hindus in Bali. The implementation of yajña in Bali in the modern era in a certain quantity and capacity tends to display its festive side, so that the value or main purpose of the implementation of yajña is doubtful. In addition, there are 3 specific problems that must be studied and evaluated in this research, including the concept of Causal Euphoria Ritual Yajña, then the causes of the emergence of Causal Euphoria Ritual Yajña (CERiYa) among the younger generation of Hindus in Bali, and solutions in overcoming Causal Euphoria Ritual Yajña Implementation (CERiYa) among the younger generation of Hindus in Bali. Basically, the purpose of this research is to contribute thoughts to the dynamics of religious life, especially in the field of tradition and culture. Therefore, in the future, the implementation of yajña is not only focused on the systematics of implementation, but also understands its philosophical value.Given that this research is a type of Qualitative research, the data collection used literature and document recording techniques. The results of the analysis and evaluation show that Causal Euphoria of Yajña Ritual is a number of causes of the emergence of excessive excitement in a yajña ritual. The causes in question are largely due to several things, such as a low level of understanding of religious philosophy, a wrong religious perspective, and the unstoppable flow of modernization and globalization. Based on this analysis, it can be concluded that there needs to be an improvement in the field of Hindu religious education, especially regarding yajña in in-formal, formal, and non-formal environments that are not only centered on the theoretical aspects but also on the quality of educators or religious instructors and the deepening of yajña philosophy.